Macrophage-Specific NF-κB Activation Dynamics Can Segregate Inflammatory Bowel Disease Patients - Papoutsopoulou, Stamatia; Burkitt, Michael D.; Bergey, François; England, Hazel; Hough, Rachael; Schmidt, Lorraine; Spiller, David G.; White, Michael H. R.; Paszek, Pawel; Jackson, Dean A.; Martins Dos Santos, Vitor A. P.; Sellge, Gernot; et al. (Frontiers in Immunology, 2019)
The heterogeneous nature of inflammatory bowel disease (IBD) presents challenges, particularly when choosing therapy. Activation of the NF-B transcription factor is a highly regulated, dynamic event in IBD pathogenesis. Using a lentivirus approach, NF-B-regulated luciferase was expressed in patient macrophages, isolated from frozen peripheral blood mononuclear cell samples. Following activation, samples could be segregated into three clusters based on the NF-B-regulated luciferase response. The ulcerative colitis (UC) samples appeared only in the hypo-responsive Cluster 1, and in Cluster 2. Conversely, Crohn’s disease (CD) patients appeared in all Clusters with their percentage being higher in the hyper-responsive Cluster 3. A positive correlation was seen between NF-B-induced luciferase activity and the concentrations of cytokines released into medium from stimulated macrophages, but not with serum or biopsy cytokine levels. Confocal imaging of lentivirally-expressed p65 activation revealed that a higher proportion of macrophages from CD patients responded to endotoxin lipid A compared to controls. In contrast, cells from UC patients exhibited a shorter duration of NF-B p65 subunit nuclear localisation compared to healthy controls and CD donors. Analysis of macrophage cytokine responses and patient metadata revealed a strong correlation between CD patients who smoked and hyper-activation of p65. These in vitro dynamic assays of NF-B activation in blood-derived macrophages have the potential to segregate IBD patients into groups with different phenotypes and may therefore help determine response to therapy.